ANALISIS PENERAPAN TARIF PERDA NO 3 TAHUN 2011 ATAS RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN PADA MASYARAKAT KECAMATAN MALALAYANG DAN KECAMATAN SARIO KOTA MANADO - Jiaw, Pamela Firginia; Sabijono, Harijanto; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Retribution constituting regional levies on payment of services given by the government which one of it is general service levy which contains levy waste or hygiene. This study aims to (1) analyze implementation of tariff policy Levy Waste or Hygiene based on regional regulations Law Number (No.) 3 of 2011; (2) analyze tariff capability to covering operational costs of Levy Waste or Hygiene. The method used in this research is descriptive method. This study use the qualitative approach. The results shows, tariff policy Levy Waste or Hygiene implemented by Malalayang subdistrict and Sario subdistrict has been carried out in accordance with regional regulations Law Number (No.) 3 of 2011 and Levy Waste or Hygiene’ tariff incompetent yet of covering operational costs thoroughly. The Local Government should re-collect data to compulsory levy whose unreached yet as of be able to increasing revenue in additional to cover the operational costs.Keywords: Policy, Tariff, Regional Reglations, Levy Waste or Hygiene, Capability, Operational Costs